Evaluation of rotational resistance of bogies. (May 2017) - Tanaka, T; Iida, K; Suzuki, M; Iida, T; Watanabe, N; Miyamoto, T
To prevent derailment such as flange-climbing derailment, precise understanding of the vehicle dynamics is important. In this study, the authors have developed a bogie rotational resistance test machine which has many innovative functions to understand the characteristics of railway bogies. The test machine can measure the rotational resistance of a bogie connected to a carbody. By using this machine, some distinctive characteristics of the rotational resistance have been clarified. As a result, a modified simulation model was constructed based on the test result, and it enabled a more accurate analysis of vehicle dynamics during the curve passage.